2023
DOI: 10.1039/d2fo03975c
|View full text |Cite
|
Sign up to set email alerts
|

Bovine milk-derived extracellular vesicles prevent gut inflammation by regulating lipid and amino acid metabolism

Abstract: Inflammatory bowel disease (IBD) is a global health problem in which metabolite alteration plays an important pathogenic role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Mammary gland-derived extracellular vesicles carry unique RNA, proteins, lipids, and DNA, possessing anti-degradation, antioxidant, and anti-inflammatory biological properties ( 100 ). Studies have found these vesicles to play a crucial role in the treatment of intestinal inflammation and colitis.…”
Section: Mammary Gland-derived Extracellular Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Mammary gland-derived extracellular vesicles carry unique RNA, proteins, lipids, and DNA, possessing anti-degradation, antioxidant, and anti-inflammatory biological properties ( 100 ). Studies have found these vesicles to play a crucial role in the treatment of intestinal inflammation and colitis.…”
Section: Mammary Gland-derived Extracellular Vesiclesmentioning
confidence: 99%
“…Additionally, mammary gland-derived extracellular vesicles can reduce intestinal epithelial damage, restore intestinal tight junction proteins, and regulate inflammation and cellular homeostasis, which holds significance for inflammatory bowel diseases such as necrotizing enterocolitis and inflammatory bowel disease ( 102 , 103 ). The latest research indicates that mammary gland-derived extracellular vesicles can modulate lipid and amino acid metabolism in healthy mice and may alter the metabolomic characteristics of DSS-induced colitis in mice, particularly increasing levels of lipid anti-inflammatory metabolites and decreasing levels of fecal amino acids, which could be a primary driving force in alleviating colitis ( 100 ). Moreover, these vesicles have demonstrated potential applications in other inflammatory disease domains.…”
Section: Mammary Gland-derived Extracellular Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, bovine milk-derived exosomes can attenuate DSS-induced UC in the mice by remodeling and optimizing the abundance of intestinal flora, regulating intestinal gene expression, and restoring the structure and integrity of the intestinal surface epithelium [ 140 ]. Moreover, bovine milk-derived exosome was reported to help in the restoration of metabolic abnormalities induced by DSS-induced UC in the mice, and also prevent intestinal inflammation by regulating lipid and amino acid metabolism, thereby providing new insights into the identification and utilization of lactation-derived exosomes as potential regulators for the prevention and treatment of IBD [ 141 ]. Goat milk-derived exosomes were also reported to show anti-inflammatory and immunomodulatory effects, hence can reduce LPS-induced inflammation of the porcine jejunal epithelial cells (IPEC-J2 cells) and also restore cellular homeostasis by decreasing the level of expressions of IL18, IL12p40, matrix metalloproteinase 9 (MMP9) and nitric oxide synthase (NOS2), but increase the level of expressions of mucin 2 (MUC2), epstein-barr virus-induced gene 3 (EBI3), and IL-8 [ 142 ].…”
Section: Therapeutic Effects Of Milk-derived Exosomes On Intestinal D...mentioning
confidence: 99%
“… IL-6 and TNF-α↓; Dubosiella , Bifidobacterium , UCG-007 , Lachnoclostridium , Lachnospiraceae ↑; butyrate and acetate↑ [ 140 ] Cow milk DSS-induced UC Mice Regulates the concentrations of lipids and amino acids in both fecal samples and colonic tissues, recover the metabolic abnormalities caused by inflammation. Acetate, butyrate, L-arginine↑; C13:0, C15:1, C20:1, C20:2, C20:5, C22:6↓; L-valine, L-serine and L-glutamate↓ [ 141 ] Goat milk LPS-induced IPEC-J2 cells Increases the antimicrobial peptides, defensins and toll like receptors, induce the preferential expression of the anti-inflammatory, improve intestinal homeostasis. IL18, IL12p40, MMP9, NOS2↓; MUC2, EBI3, IL-6, IL-8↑ [ 142 ] Human breast milk LPS-induced NEC mice (intestinal epithelial cells, IEC-6 cells) Protects against NEC and attenuate TLR4 signaling via EGF/EGFR activation, inhibit enterocyte apoptosis and restore enterocyte proliferation TLR4, NF-κB, IL-6, IL-1β, GSK3β, iNOS↓; EGFR, PCNA↑ [ 150 ] Human breast milk hypoxia and gavage-induced NEC rat and human normal intestinal epithelial cell line (FHC) Protects against NEC by promoting intestinal cell proliferation and migration Ileum injury area↓; villous integrity, proliferation and migration↑ [ 152 ] Human breast milk H 2 O 2 -induced NEC (intestinal stem cells, ISCs) Increases ISC viability, protect ISCs from oxidative stress injury via the Wnt/β-catenin signaling pathway Axin2, c-Myc, and Cyclin D1↑ [ 153 ] Human breast milk LPS-induced NEC rat (intestinal epithelial cells, IEC-6 cells) Decreases the incidence and severity of experimental NEC, increase IEC proliferation and decrease apoptosis, protect IEC from injury in vitro Cell proliferation rate↑; Late apoptotic cells↓; intestinal damage↓; NEC incidence↓ …”
Section: Therapeutic Effects Of Milk-derived Exosomes On Intestinal D...mentioning
confidence: 99%